Factors influencing the intention of IPTA students towards entrepreneurship in Kelantan - Divaney Ravichandar; Nur Sarah Alyaa Rosli; Siti Suriatey Ithnen; Fatin Nasuha Abd Karim (2024)
Factors that influence entrepreneurial intention among IPTA students towards entrepreneurship in Kelantan. Entrepreneurial intentions are able to change the way of thinking and behavior of IPTA students in Kelantan to make the field of entrepreneurship a career choice in the future. The objective of this study is to determine the relationship between entrepreneurial intention and perceived social rule, attitude, perceived support and education among IPTA students in Kelantan. This study focuses on four independent variables consisting of perceived social rule, attitude, perceived support and education that can influence the dependent variable which is entrepreneurial intention among IPTA students in Kelantan. This study also conducted a survey through a questionnaire to 377 IPTA students (UMK & UiTM) in Kelantan. The researcher also used SPSS version 27 to analyze the data and obtain the results of this study. The researcher discusses the findings of the study and examines whether the objectives of this study can be achieved or not. The results of this study also show that all independent variables (perceived social rule, perceived support, attitude and education) have a significant relationship between the dependent variable (Entrepreneurial Intention). Therefore, all hypotheses were tested, none of the hypotheses were rejected and accepted in this study.